Maximizing ERP Benefits with Enterprise Architecture: A Holistic Approach - Wedha, Bayu Yasa; Hindarto, Djarot (Information Technology and Science (ITScience), 2023)
Enterprise Resource Planning systems must strategically align with Enterprise Architecture to maximize benefits. In a business environment that is undergoing rapid change, organizations increasingly rely on ERP systems to integrate and streamline operations. However, the complete potential of ERP benefits may only be realized with an approach encompassing the entire organizational architecture. This study examines the importance of aligning ERP implementation with EA principles to establish a cohesive technological ecosystem. Organizations can facilitate seamless interactions and data flows by harmonizing business processes, data structures, applications, and technology infrastructure, allowing for efficient decision-making and resource optimization. The abstract describes how EA provides a structured blueprint to guide the integration of ERP systems, assuring compatibility, minimizing redundancies, and maximizing overall system efficiency. By conducting a comprehensive literature review and case study analysis, this study demonstrates the benefits of an integrated approach, including increased visibility, reduced operational divisions, improved scalability, and faster response to changes. The abstract also emphasizes the role of EA in adapting and evolving ERP systems as business requirements change, enabling organizations to resolve challenges and proactively leverage emerging technologies. Overall, this research contributes to a deeper understanding of the symbiotic relationship between EA and ERP by highlighting their combined ability to drive business growth, agility, and competitiveness. The abstract emphasizes the importance of strategic alignment. It guides practitioners, researchers, and decision-makers who wish to maximize the benefits of ERP implementations through a holistic Enterprise Architecture approach.